BLEND: a fast, memory-efficient and accurate mechanism to find fuzzy seed matches in genome analysis. Issue 1 (20th January 2023) - Firtina, Can; Park, Jisung; Alser, Mohammed; Kim, Jeremie S; Cali, Damla Senol; Shahroodi, Taha; Ghiasi, Nika Mansouri; Singh, Gagandeep; Kanellopoulos, Konstantinos; Alkan, Can; Mutlu, Onur
Abstract: Generating the hash values of short subsequences, called seeds, enables quickly identifying similarities between genomic sequences by matching seeds with a single lookup of their hash values. However, these hash values can be used only for finding exact-matching seeds as the conventional hashing methods assign distinct hash values for different seeds, including highly similar seeds. Finding only exact-matching seeds causes either (i) increasing the use of the costly sequence alignment or (ii) limited sensitivity. We introduce BLEND, the first efficient and accurate mechanism that can identify both exact-matching and highly similar seeds with a single lookup of their hash values, called fuzzy seed matches. BLEND (i) utilizes a technique called SimHash, that can generate the same hash value for similar sets, and (ii) provides the proper mechanisms for using seeds as sets with the SimHash technique to find fuzzy seed matches efficiently. We show the benefits of BLEND when used in read overlapping and read mapping. For read overlapping, BLEND is faster by 2.4×–83.9× (on average 19.3×), has a lower memory footprint by 0.9×–14.1× (on average 3.8×), and finds higher quality overlaps leading to accurate de novo assemblies than the state-of-the-art tool, minimap2. For read mapping, BLEND is faster by 0.8×–4.1× (on average 1.7×) than minimap2. Source code is available at https://github.com/CMU-SAFARI/BLEND .